Limnic Rendzinas in the Mazurian Lakeland (NE Poland) - Lemkowska Bożena; Sowiński Paweł (Soil Science Annual, 2018)
Several shallow lakes have been drained to make way for additional arable land or pasture in the Mazurian Lakeland (NE Poland) since the 19th century. As a result of these hydrotechnical works, the water level usually decreased by approximately 6 m. Bottom sediments of the former lakes were transformed into surface limnic soils. Part of them, developed from highly calcareous gyttja, may be called limnic rendzinas. However, the present position of these soils in the Polish Soil Classification is unclear. Where the lake has undergone a natural terrestrialisation, the gyttja is covered with peat and mursh. The raw gyttja soils differ in type of organic matter forming the topsoil horizon and are subject to further transformation, the direction of which depends on the sequence of sediments in the profile, mursh formation, mineral admixture and adjoining colluvial phenomena. Common features of all these soils are high content of calcium carbonate in the surface horizons, alkaline reaction, high groundwater level and periodical flooding. The paper presents the variability of limnic rendzinas based on many examples from the Mazurian Lakeland (NE Poland). Finally, new type additions were suggested to the next edition of the Polish Soil Classification.